2021
DOI: 10.1021/acs.accounts.0c00670
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State NMR of Membrane Proteins in Lipid Bilayers: To Spin or Not To Spin?

Abstract: Metrics & MoreArticle Recommendations CONSPECTUS: Membrane proteins mediate a plethora of cellular functions and represent important targets for drug development. Unlike soluble proteins, membrane proteins require native-like environments to fold correctly and be active. Therefore, modern structural biology techniques have aimed to determine the structure and dynamics of these membrane proteins at physiological temperature and in liquid crystalline lipid bilayers. With the flourishing of new NMR methodologies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 81 publications
0
13
0
Order By: Relevance
“…The structural and functional properties of DWORF are unique among the regulins. Structurally, DWORF consists of a short, cytoplasmic helix (residues 1-13), a flexible linker centered around Pro 15 (residues 14-16), and a transmembrane helix (residues 17-35) (Figure 4A) [25,71]. Overall, the structural features of DWORF (Figure 4A) are similar to PLN (Figure 2A), though DWORF is a much shorter peptide (35 residues versus 52 residues, respectively).…”
Section: Dwarf Open Reading Frame (Dworf)-a Little Regulin With a Big Heartmentioning
confidence: 94%
“…The structural and functional properties of DWORF are unique among the regulins. Structurally, DWORF consists of a short, cytoplasmic helix (residues 1-13), a flexible linker centered around Pro 15 (residues 14-16), and a transmembrane helix (residues 17-35) (Figure 4A) [25,71]. Overall, the structural features of DWORF (Figure 4A) are similar to PLN (Figure 2A), though DWORF is a much shorter peptide (35 residues versus 52 residues, respectively).…”
Section: Dwarf Open Reading Frame (Dworf)-a Little Regulin With a Big Heartmentioning
confidence: 94%
“…Among the biomolecules of medical interest, membrane proteins such as GPCR suffer from spectral crowding induced by conformational plasticity [70] that, for most of them, limits their access for NMR investigation. High-magnetic field and MAS spinning above 60 kHz rotation frequency demonstrated that sensitivity and 1 H resolution can be significantly improved, notably for microcrystalline proteins available in small amounts [71] but also for membrane proteins [41]. Selective 13 C-isotope labelling schemes should alleviate the spectral crowding induced by the high percentage of hydrophobic amino acids present in -helical membrane proteins and therefore, they could help the detection of conformational plasticity of biologically systems by solid-state NMR.…”
Section: Discussionmentioning
confidence: 99%
“…Previous data on GB1 and Vpu recorded at different temperatures have shown their importance for the optimization of NMR sensitivity [37,38]. Most of the ssNMR data acquired on membrane proteins in lipids are based on CP rather than the INEPT element [39][40][41] since dipolar coupling transfer (through space) is expected to be more efficient than scalar (through bond) one. Scalar-based methods such as INEPT and notably INADEQUATE have been shown to work well for microcrystalline super-oxide dismutase under ultrafast magic-angle spinning [42].…”
Section: Introductionmentioning
confidence: 99%
“…The first approach involves the uniaxial alignment of protein molecules in lipid bilayers either mechanically on glass plates or with lipid bicelles that spontaneously align when placed in a magnetic field (section ). , This approach is primarily useful for investigating the structure, dynamics, and orientation of different transmembrane helices or membrane-bound segments of proteins and their complexes. , Magic angle spinning (MAS) is the second approach in ssNMR for characterizing the structure of biomolecules and has become an essential tool due to major developments in the last two decades. MAS approach entails mechanical spinning of biomolecular samples in rotors (cylindrical sample holders with turbines that spin using air) about an axis inclined at an angle of (∼54.7356°, the eponymous magic angle) with respect to the direction of the static magnetic field (section ).…”
Section: Introductionmentioning
confidence: 99%